2018
DOI: 10.3389/fnagi.2018.00375
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep Quality Associates With Decreased Functional and Structural Brain Connectivity in Normative Aging: A MRI Multimodal Approach

Abstract: Sleep is a ubiquitous phenomenon, essential to the organism homeostasis. Notwithstanding, there has been an increasing concern with its disruption, not only within the context of pathological conditions, such as neurologic and psychiatric diseases, but also in health. In fact, sleep complaints are becoming particularly common, especially in middle-aged and older adults, which may suggest an underlying susceptibility to sleep quality loss and/or its consequences. Thus, a whole-brain modeling approach to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 91 publications
(104 reference statements)
2
24
2
Order By: Relevance
“…In contrast to our findings, several DTI studies (Khalsa et al, 2017;Sexton et al, 2017;Amorim et al, 2018;Takeuchi et al, 2018) reported that worsened sleep quality was associated with disrupted WM tracts of frontal, temporal, occipital, and subcortical regions. It should be noted that the above studies are varying with demographics of the participants (e.g., gender and ages), sample size, MRI sequences, and the statistical methods FIGURE 1 | Significant voxel-wise correlations between diffusion metrics of brain white matter (WM) tracts and BDI scores using TBSS (5000 permutations, FWER at p < 0.05).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, several DTI studies (Khalsa et al, 2017;Sexton et al, 2017;Amorim et al, 2018;Takeuchi et al, 2018) reported that worsened sleep quality was associated with disrupted WM tracts of frontal, temporal, occipital, and subcortical regions. It should be noted that the above studies are varying with demographics of the participants (e.g., gender and ages), sample size, MRI sequences, and the statistical methods FIGURE 1 | Significant voxel-wise correlations between diffusion metrics of brain white matter (WM) tracts and BDI scores using TBSS (5000 permutations, FWER at p < 0.05).…”
Section: Discussioncontrasting
confidence: 99%
“…Poor sleep quality has been associated with changes of brain structure and function by using advanced magnetic resonance imaging (MRI) techniques (Sexton et al, 2014;Spira et al, 2016;Amorim et al, 2018). Of these MRI modalities, diffusion tensor imaging (DTI) (Le Bihan et al, 2001), which quantifies three-dimensional displacements of water molecules along axons, reflects white matter (WM) microstructure connecting distributed brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…31 Poor sleep quality is associated with brain changes, such as reduced functional connectivity and decreased gray-matter volume, as well as an increased risk for age-associated cognitive impairment and Alzheimer disease. 32,33 It is unclear whether the act of looking at screens or media content disrupts sleep; however, it is well-known that the wavelength of light exposure affects the circadian rhythms that govern sleep. Computer and phone light-emitting diode (LED) screens emit slow wave, blue light that interferes with circadian rhythms.…”
Section: Sleepmentioning
confidence: 99%
“…More recently, using a whole‐brain multimodal MRI approach 86 participants were investigated to explore the association between subjective sleep quality (PSQI global score) and functional and structural connectivity. Both measures decreased in association with poor sleep (Amorim et al, ). In related work, a structural MRI study carried out in 448 community‐dwelling older adults showed that poor sleep quality was associated with reduced global FA and increased global axial and radial diffusivity values of frontal white matter tracts (Sexton et al, ), thus suggesting that sleep quality is linked to white matter microstructure.…”
Section: Sleep and Myelinmentioning
confidence: 99%